Peran H. Wagirin Arman terhadap Voting Behavior di Hamparan Perak Tahun 2009 - TOMMY IMANUEL TARIGAN (Politeia: Jurnal Ilmu Politik, 2015)
Local elite is a group of people who have a GPA higher than others. Because of that, political elite can influence people's behavior. H. Arman Wagirin categorized as local elite. He has influenced people's behavior, especially in Kecamatan Hamparan Perak in the 2009 elections. This is a study about the role of H. Wagirin Arman on voting behavior in the Kecamatan Ham-paran Perak in 2009. The focus is how the role of H. Wagirin in shaping voter behavior in the legislative elections in the Kecamatan Hamparan Perak. This study find there are three impor-tant things that mark the role of H. Arman Wagirin the formation of communities in the Kecamatan Hamparan Perak voting behavior. First, the emotional closeness H. Arman Wagirin with various community groups; Second, the public perception of H. Wagirin Arman; Third, remains at the heart of societ. The method of this study is descriptive-qualitative. This study is using political behaviour as the approach and the data collection is using field research.Keywords: Money politics, political behaviour, rationality of the voter.